2020
DOI: 10.1111/jora.12583
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Risk for Adolescent Cognitive Control and Emerging Risk‐Taking Behaviors

Abstract: This study examined whether cognitive control mediated the association between socioeconomic status (SES; composite of income‐to‐needs ratio and parent education) and changes in risk‐taking behaviors. The sample included 167 dyads of adolescents (53% male; Mage = 14.07 years at Time 1) and their parents, assessed annually across 4 years. Parents reported socioeconomic variables at Time 1. Adolescents reported risk‐taking behaviors at Times 1 and 4, and completed a functional magnetic resonance imaging cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
(79 reference statements)
1
14
0
Order By: Relevance
“…Consistent with H3, the study confirmed self-control as another important mediator of the relationship between SES and adolescents’ risk-taking behavior. This essentially coheres with previous findings that low SES is usually associated with lower levels of self-control among adolescents, indirectly leading to an increased incidence of risk-taking behaviors that hinder physical and mental health ( Brieant et al, 2020 ). One reason for this may be the impact of low SES on individual cognitive neurodevelopment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with H3, the study confirmed self-control as another important mediator of the relationship between SES and adolescents’ risk-taking behavior. This essentially coheres with previous findings that low SES is usually associated with lower levels of self-control among adolescents, indirectly leading to an increased incidence of risk-taking behaviors that hinder physical and mental health ( Brieant et al, 2020 ). One reason for this may be the impact of low SES on individual cognitive neurodevelopment.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies on brain mechanisms have also implicated cognitive control in demonstrating that SES has a significant indirect impact on changes in adolescents’ risk-taking behavior. Adolescents from families with lower SES exhibit lower levels of cognitive control, increasing their tendency to take risks ( Brieant et al, 2020 ). It is therefore likely that poor SES exacerbates the negative effects of low self-control on risk-taking behavior during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, Spielberg et al (2015) found increased activity in the anterior cingulate during response inhibition over a two-year period was associated with poorer inhibitory control among females, but not males, from lower SES backgrounds based on the Hollingshead Four-Factor Index of SES, which includes household education and occupational prestige. In addition, behavioral studies of inhibitory performance and SES (i.e., including parental education, income, and neighborhood poverty) have found significant relationships between lower SES and lower inhibitory control performance 39 , 42 44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, parental education was not associated with IFG activity during inhibitory control or with inhibitory performance. Other recent studies showed that poverty is associated with performance on cognitive control tasks 43 , and that lower SES is associated with reduced inhibitory control on behavioral tasks, despite not finding corresponding effects in the brain 44 . Although these results support the notion that early socioeconomic adversity of different types may shape the development of inhibitory control, more research is needed regarding how parental education affects behavioral and brain measures of response inhibition, a key executive function in avoiding risky behaviors and protecting health.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, living in vulnerable conditions, particularly as a child, may be a driver for reduction in performance of functions associated with the prefrontal cortex-that have been independently associated with SA-such as social cognition (SC) (includes decision-making, emotional processing, Theory of Mind (ToM), and empathy), uid intelligence (FI), crystallized intelligence (CI), and executive functions (EF) [7,8,9,10,11,12]. Given the behavioral control exhibited by these cognitive functions, it has been suggested that adolescents living in poverty who exhibit de cits in these functions may partake in resultant maladaptive behaviors that thwart SA [13,14,15,16,17,18,19,20] The dynamics, precedents, and interactions of these cognitive functions in the context of SA and social vulnerability, however, are not yet fully understood. By elucidating the ways in which these cognitive concepts work together and separately in predicting social outcomes, we might better understand the role of speci c variables in predicting SA.…”
Section: Introductionmentioning
confidence: 99%